Internal Controls and Conditional Conservatism - Goh, Beng Wee; Li, Dan (The Accounting Review, 2011)
ABSTRACT: This study examines the relation between internal controls and conditional conservatism (“conservatism”), also referred to as timely loss recognition. Using a sample of firms that disclose material weaknesses (MWs) in internal controls under the Sarbanes-Oxley Act (SOX), we find a positive relation between internal control quality and conservatism. Specifically, firms with MWs exhibit lower conservatism than firms without such weaknesses. Further, firms that disclose MWs and subsequently remediate these weaknesses exhibit greater conservatism than firms that continue to have MWs. Overall, these results are consistent with strong internal controls acting as a mechanism that facilitates conservatism. Our study contributes to the literature on the reporting effects of strong versus weak internal controls.